Wednesday

October 22, 2014

October 22, 2014

Posted by **cory** on Sunday, March 16, 2014 at 3:58pm.

- mat 116 -
**Steve**, Sunday, March 16, 2014 at 4:43pm(2x)^3 + (2^x)^3

that's a sum of cubes, so

(2x + 2^x)((2x)^2 - (2x)(2^x) + (2^x)^2)

(2x + 2^x)(4x^2 + 2x*2^x + 2^2x)

I'm not sure that's any simpler.

Maybe you just wanted

8x^3 + 2^3x

?

**Answer this Question**

**Related Questions**

MAT 116 - Use the distributive property to rewrite the expression (a+8)4= (...

algebra - math question: you want to mat and frame a 5x 7 photograph. The ...

mat 116 - -8x-27=-32 1/3 Thank you for your help.

mat/116 - -4 -3y>11

mat 116 - help

mat 116 - What is the coefficients of y=-2x-4 y=-2x+1

Mat 116 - Hello

mat/116 - Solve 8x - (4x+4) =4

Mat 116 - -2x>1/9 {xix_ _}

Mat 116 - What is the solution of the system 7r - 5s = 36 and 5r + 7s = 68